Head-Related Transfer Functions for Dynamic Listeners in Virtual Reality - Rummukainen, Olli S.; Robotham, Thomas; Habets, Emanuël (Applied Sciences, 2021)
In dynamic virtual reality, visual cues and motor actions aid auditory perception. With multimodal integration and auditory adaptation effects, generic head-related transfer functions (HRTFs) may yield no significant disadvantage to individual HRTFs regarding accurate auditory perception. This study compares two individual HRTF sets against a generic HRTF set by way of objective analysis and two subjective experiments. First, auditory-model-based predictions examine the objective deviations in localization cues between the sets. Next, the HRTFs are compared in a static subjective (N = 8) localization experiment. Finally, the localization accuracy, timbre, and overall quality of the HRTF sets are evaluated subjectively (N = 12) in a six-degrees-of-freedom audio-visual virtual environment. The results show statistically significant objective deviations between the sets, but no perceived localization or overall quality differences in the dynamic virtual reality.
CRIS-Team WoS Importer:2021-08-06